A retrospective study of zoonotic tuberculosis among livestock farmers of Lahore district using one health approach (Journal of Advanced Veterinary and Animal Research, 2024)
Objectives: Tuberculosis (TB) affects humans and animals regardless of species type, causing huge economic losses and deaths worldwide. However, the mechanisms and risk factors of zoonotic transmission are not well known in Pakistan. The current study aimed to identify the potential risk factors associated with TB in farmers and their animals, particularly exposure to infected animals in Lahore District, Pakistan. Materials and Methods: The study consisted of two components utilizing the concept of One Health. In the first component, a retrospective case-control study of human subjects (cases = 25, control = 25) was conducted from December 2021 to July 2022. In the second component, a cross-sectional analysis of the cattle owned by selected participants (TB cases and healthy controls) was completed in the Lahore district. A single intradermal tuberculin skin test was used to determine TB infection in cattle. Results: A total of 25 TB cases and 25 healthy controls were enrolled. Males in cases were found (OR = 0.01, 95% CI: 0.0002–0.29, p = 0.014) less likely to get TB, cases older than 35 years(OR = 1.13 (95% CI: 1.05–1.24, p = 0.004), unmarried cases (OR = 32.20, 95% CI: 2.92–819.03, p = 0.014), being a smoker (OR = 21.87, 95% CI: 2.80–395.82, p = 0.011), and keeping animals inside the home (OR = 9.92, 95% CI: 1.29–134.61, p = 0.047) were identified as significant predictors of TB in humans in the final multivariable logistic regression. Out of 175 tested animals, 3/65 animals belonging to the cases and 1/110 animals belonging to the controls were found positive. The animals belonging to the TB cases were (OR = 7.76, 95% CI; 0.79–76.02) more likely to have a positive Single Comparative Intradermal Tuberculin Test test. The prevalence of bTB in animals belonging to the cases was 4.6% (95% CI, 1.26–12.58) compared to 0.9% (95% CI, 0.04–4.67) in animals of the control group. Conclusion: This study identified potential risk factors that could contribute to the complex web of TB transmission between humans and animals. Our findings could provide data to inform policy-making and intervention strategies to reduce TB’s burden in both populations. Embracing a holistic One Health perspective is imperative to effectively combat this shared health threat.J. Adv. Vet. Anim. Res., 11(4): 967–978, December 2024http://doi.org/10.5455/javar.2024.k847